Design and Implementation of a Communication Campaign on Best Management Practice for Forest Nurseries - Gravoso, Rotacio; Gregorio, Nestor; Gerona, Annabelle; Godoy, Jayson (Annals of Tropical Research, 2010)
High quality tree seedlingss are critical factors which determine the success of tree plantation projects. To produce high quality seedlings, nursery operators need to apply appropriate nursery management practices. However, tree seedlings produced by nursery operators in the Philippines are often of low quality, due in part to weak organization in the nursery sector and lack of skills in the application of nursery practices among nursery operators. The Ჹ-seedling Project or Seedling Enhancement Project funded by the Australian Centre for International Agricultural Research (ACIAR) is being implemented in Leyte and Northern Mindanao to remedy this skills gap. The project includes a communication component to promote widespread adoption of best management practice in forest nurseries. Following the strategic communication approach, information dissemination activities in the project are based on the needs of the target users. Training workshops have been held on producing high quality seedlings. Also, communication materials have been developed for nursery operations, including a training guide, videos instructional posters on Q-seedling production technologies, and a jingle about Q-seedlings. This paper describes the design and use of these communication materials.